THE INTEGRATION OF SMALL AND MEDIUM-SIZED ENTERPRISES INTO GLOBAL VALUE CHAIN - Sikharulidze, David (European Scientific Journal, ESJ, 2014)
Intensifying globalization of production and trade is causing growing competitive pressures for developing country producers. Accelerated technological advancements and trade and investment liberalization increasingly make fragmenting of activities in all stages of a production value chain possible. Some of these segmented activities can be performed in various locations across the globe and reintegrated again through production systems of global value chains and global production networks. A group of leading transnational corporations are playing a key role in organizing and controlling these production systems, benefiting from location differences in costs, infrastructure, capabilities in manufacturing, marketing and logistic, and in trade and investment regimes. The objective of this research is to explain the role of global value chain in building and enhancing productive capacities of developing countries and economies in transition. By participating in a global value chain, domestic firms, particularly small and medium-scale enterprise (SMEs) can access technology, upgrade skills and improve their competitiveness. It can help developing country producers to enter foreign markets, earn more foreign currencies, diversify their exports, and most importantly to get new skills, knowledge and technology—all considered as key factors for productivity enhancement and growth.